2008
DOI: 10.2310/7750.2007.00034
|View full text |Cite
|
Sign up to set email alerts
|

Becker Nevus on the Lower Limb: Case Report and Review of the Literature

Abstract: Background: Becker nevus is a hamartoma with brown hyperpigmentation and hypertrichosis that usually affects young males.It has a predilection for the upper half of the trunk and proximal upper extremity.Objective: This is a case report of a 38-year-old male with a Becker nevus without hypertrichosis on the lower limb and a review of the literature.Results: Including our case report, 12 cases of Becker nevus on the lower limb were identified in the English literature (8 males and 4 females). It has never been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Regarding localization, 69.48% of the BN lesions were observed in the shoulder girdle in accordance with the literature, 1,3 seven cases were found in the arms and three in the thighs. In the literature only eight cases were reported in the lower limb 5 . Interestingly three individuals had two BN lesions, which is also considered very rare 6 .…”
Section: Localization Of the Becker’s Nevimentioning
confidence: 99%
“…Regarding localization, 69.48% of the BN lesions were observed in the shoulder girdle in accordance with the literature, 1,3 seven cases were found in the arms and three in the thighs. In the literature only eight cases were reported in the lower limb 5 . Interestingly three individuals had two BN lesions, which is also considered very rare 6 .…”
Section: Localization Of the Becker’s Nevimentioning
confidence: 99%
“…At least 15 cases of BN on the lower limbs of adolescents were identified in the English literature (11 males and 4 females). (11,15) Our data revealed that 7.6% (59 cases) showed predilection for lower limbs; buttocks in 4.5%, thighs in 2.5%, and legs in 1.1%. In a very recent article of childhood series of BN, 15 cases have been documented on legs (12.8%).…”
Section: Discussionmentioning
confidence: 65%
“…Subsequently, 11 more cases of Becker nevus of the leg have been reported. 4 In 2 patients, the reports explicitly noted the absence of hypertrichosis. In 2 female patients, Becker nevus was associated with localized lipoatrophy: a 14-year-old girl with a softtissue defect on the ventral aspect of her thigh and a 45-yearold woman with lipoatrophy on the right thigh.…”
Section: Becker Nevus Of the Leg With Lipoatrophymentioning
confidence: 99%